Safety, tolerability, pharmacokinetic, and pharmacodynamic characteristics of vutiglabridin: A first‐in‐class, first‐in‐human study - Joo Young Na; Deok Yong Yoon; Hyounggyoon Yoo; SeungHwan Lee; Kyung‐Sang Yu; In‐Jin Jang; Sang‐Ku Yoo; Youngah Kim; Jaeseong Oh (Wiley, 2022)
Abstract This study aimed to evaluate the safety, tolerability, pharmacokinetics, and pharmacodynamics of vutiglabridin, a potential anti‐obesity treatment under development, for the first time in humans. A randomized, placebo‐controlled, single‐ and multiple‐ascending dose study (SAD and MAD, respectively) was performed in healthy Koreans and Whites. Subjects randomly received a single oral dose of 30-720 mg vutiglabridin or placebo at a ratio of 8:2 in the SAD study or 240-480 mg vutiglabridin or placebo once daily for 14 days in the MAD study. Food effect was also evaluated in 240 mg single dose group. Pharmacokinetics were evaluated through plasma concentrations, and pharmacodynamic biomarkers related to obesity or inflammation were analyzed. Safety and tolerability were assessed throughout the study. Single and multiple doses of vutiglabridin were generally well‐tolerated. The pharmacokinetic parameters show less than dose‐proportionality increase, and plasma concentrations increased more than two‐fold after multiple administrations. The mean half‐life of Koreans and Whites in the MAD study was 110 and 73 h, respectively. The systemic exposure of vutiglabridin was significantly increased when taken with a high‐fat meal, and the systemic exposure was lower in Whites than in Koreans. Vutiglabridin was well‐tolerated in healthy Koreans and Whites. The plasma concentration increased less than the dose‐proportionality manner. These results justify further investigation of vutiglabridin in patients with obesity.